Establishing carbon–carbon double bond position and configuration in unsaturated fatty acids by gas-phase infrared spectroscopy. Issue 10 (15th February 2023) - Kirschbaum, Carla; Young, Reuben S. E.; Greis, Kim; Menzel, Jan Philipp; Gewinner, Sandy; Schöllkopf, Wieland; Meijer, Gerard; von Helden, Gert; Causon, Tim; Narreddula, Venkateswara R.; Poad, Berwyck L. J.; Blanksby, Stephen J.; et al.
Abstract : 3-Pyridylcarbinol ester derivatization introduces a universal probe for cryogenic gas-phase infrared spectroscopy of fatty acids that enables assignment of the position and configuration of carbon–carbon double bonds even in the presence of isomers. Abstract : Fatty acids are an abundant class of lipids that are characterised by wide structural variation including isomeric diversity arising from the position and configuration of functional groups. Traditional approaches to fatty acid characterisation have combined chromatography and mass spectrometry for a description of the composition of individual fatty acids while infrared (IR) spectroscopy has provided insights into the functional groups and bond configurations at the bulk level. Here we exploit universal 3-pyridylcarbinol ester derivatization of fatty acids to acquire IR spectra of individual lipids as mass-selected gas-phase ions. Intramolecular interactions between the protonated pyridine moiety and carbon–carbon double bonds present highly sensitive probes for regiochemistry and configuration through promotion of strong and predictable shifts in IR resonances. Gas-phase IR spectra obtained from unsaturated fatty acids are shown to discriminate between isomers and enable the first unambiguous structural assignment of 6 Z -octadecenoic acid in human-derived cell lines. Compatibility of 3-pyridylcarbinol ester derivatization with conventional chromatography-mass spectrometry and now gas-phase IR spectroscopy paves the way for comprehensive structure elucidation of fatty acids that is sensitive to regio- and stereochemical variations and with the potential to uncover new pathways in lipid metabolism.